Kemampuan Pemecahan Masalah Calon Guru pada Materi Bangun Ruang Sisi Datar (Studi Kasus) - Bettisari Napitupulu; Agnes Teresa Panjaitan (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
This study aims to reveal preservice mathematics teachers’ understanding of problem solving on polyhedron topics. The subjects of this research is two students who have taken plane geometry course and have already learned studied polyhedron topics. The data collection is collected by providing a written test where the questions are non-routine problemand focused on Polya's problems solving. Futhermore, the subjects were interviewed twice to obtain valid data. Both subjects have already demonstrated problem-solving skills at the level of understanding problems. This is characterized by the ability to express problems in their own words. The ability to make plans is also good although there is one subject makes an inappropriate planning resulting in errors in problem solving. In carrying out the plan, one of the subjects shows the ability to present solutions that are not unique or varied, not only in the types of polyhedrons but also in the sizes of each polyhendron selected. The last part is looking back and review the solution was based on the results of interviews of them. This activity actually has been done even if it is not apparent in the answers of the written test.